### Solved Example 1

Factor `x^3 - 8`

### Solution

Rewrite 8 as `2^3`,

Comparing with `a^3 - b^3`, we get`x^3 - 2^3`

`a = x` and `b = 2`Applying the formula of difference of cubes: `a^3 - b^3 = (a - b)(a^2 + ab + b^2)`, we get

`(x - 2)(x^2 + x*2 + 2^2)`Simplifying,

`(x - 2)(x^2 + 2x + 4)`

### Solved Example 2

Factor `8a^3 - b^3`### Solution

Rewrite 8 as `2^3`,

Comparing with `a^3 - b^3`, we get,`(2a)^3 - b^3`

`a = 2a` and `b = b`Applying the formula `a^3 - b^3 = (a - b)(a^2 + ab + b^2)`, we get

`(2a - b)((2a)^2 + (2a)(b) + b^2)`Simplifying,

`(2a - b)(4a^2 + 2ab + b^2)`

### Solved Example 3

Factor `1 - x^3`

### Solution

Rewrite 1 as `1^3` (because `1^3 = 1 * 1 * 1 = 1`).

Comparing with `a^3 - b^3`, we get`1^3 - x^3`

`a = 1` and `b = x`Applying the formula `a^3 - b^3 = (a - b)(a^2 + ab + b^2)`, we get

`(1 - x)(1^2 + 1*x + x^2)`Simplifying,

`(1 - x)(1 + x + x^2)`

## No comments:

## Post a Comment